Moderating Role of Team Effectiveness on the Relationship Between Workload, Work Stress, and Turnover Intention Among Gen Z Women in Labor-Intensive Industries in Cirebon Indonesia - Seftiani, Maezar; Faatihah, Nazwah Fiena; Sidiq, Dedi Muhammad; Ramli, Haslina (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the influence of workload and work stress on the turnover intention of Gen Z female employees in large labor-intensive industries in Cirebon, Indonesia, with team effectiveness as a moderating variable. A quantitative approach was employed, with data collected from 200 respondents using a questionnaire. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results show that both workload and work stress have a positive and significant effect on turnover intention. However, team effectiveness only moderates the relationship between work stress and turnover intention, not the relationship between workload and turnover intention. This research contributes to economic growth by highlighting strategies to reduce employee turnover in labor-intensive industries, which are crucial for local economic stability and productivity. Enhancing team effectiveness can mitigate the negative impact of work stress, leading to improved employee retention and business sustainability. This study offers originality by focusing on Gen Z female employees in labor-intensive industries—a demographic and sector that remain underexplored in the Indonesian context, particularly in Cirebon. It also uniquely examines the moderating role of team effectiveness in the relationship between stress, workload, and turnover intention.